2015
DOI: 10.1111/dme.12841
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise training increases lower limb speed of strength generation during stair ascent and descent in people with diabetic peripheral neuropathy

Abstract: including titles -250 words, Total -2'948 words Funding Statement Funded by a Clinical Research Grant from the European Foundation for the Study of Diabetes (EFSD) Conflicts of InterestThe authors certify that they have NO affiliations with or involvement in any organization or entity with any financial interest in the subject matter or materials discussed in this manuscript. Novelty StatementHere we examined for the first time, the effects of a resistance exercise based intervention on speed of knee and ankle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…97 Participation in a 16 week moderate intensity resistance training intervention (1 hour per week, exercises included leg press, leg extension and ankle press) was accompanied by faster torque development during stair negotiation. 99 Taken together, these studies indicate that moderate intensity aerobic and resistance training have significant potential to improve symptoms and mitigate strength deficits in individuals with DPN.…”
Section: The Lack Of Effective Treatments For Dpn and The Role Of Phymentioning
confidence: 78%
See 1 more Smart Citation
“…97 Participation in a 16 week moderate intensity resistance training intervention (1 hour per week, exercises included leg press, leg extension and ankle press) was accompanied by faster torque development during stair negotiation. 99 Taken together, these studies indicate that moderate intensity aerobic and resistance training have significant potential to improve symptoms and mitigate strength deficits in individuals with DPN.…”
Section: The Lack Of Effective Treatments For Dpn and The Role Of Phymentioning
confidence: 78%
“…Recently, functional rates of force development were improved following resistance training in DPN. 99 The effect of resistance exercise and increased muscle mass is essential to improve glycemic control as skeletal muscle is typically responsible for the majority of whole body glucose uptake. Therefore, substantial increases in skeletal muscle mass alone would be expected to lower blood glucose.…”
Section: The Lack Of Effective Treatments For Dpn and The Role Of Phymentioning
confidence: 99%
“…This survey suggests that failure to recover from a trip is a common perceived cause of falls and may indicate a delayed reactive strategy. This could be due to slowed rate of force production in weakened muscles or sensory dysfunction, as seen in other peripheral neuropathies and older people (Handsaker et al, ; Kim & Robinson, ). A study by Nardone et al () explored reactive strategies in people with peripheral neuropathy, relating them to postural control but not to falls.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that resistance exercise training might be a useful clinical intervention for improving these abnormalities and therefore reducing fall risk. Thus, in the next study, we examined the effects of a 16-week resistance exercise training intervention on the speed of ankle and knee strength generation during stair ascent and descent in people with diabetic peripheral neuropathy [45]. In a similar design incorporating people with and without diabetic peripheral neuropathy together with people without diabetes, we assessed ankle and knee strength generation during climbing and descending stairs, and showed that after the resistance exercise intervention, these measures were significantly higher.…”
Section: Gait Studies In Diabetic Neuropathymentioning
confidence: 99%